PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN MENGGUNAKAN OBJEK LANGSUNG UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN DESKRIPSI SISWA KELAS V SDIT INSAN UATAM PEKANBARU - Dwi Sofyani (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of this study is the low value of students' essay writing skills at the SDIT Main Insan Pekanbaru. This study also aims to improve students' essay writing skills by applying cooperative learning models using objects directly to class V SDIT Main Insan Pekanbaru students. This type of research is classroom action research. The place for conducting this research was at the SDIT Insan Utama Pekanbaru school, with 22 students. The object of this research is the skill of writing a description using a direct object. Methods of collecting data using tests and observations. Instruments in the form of test questions and observation sheets. Data were analyzed by quantitative descriptive analysis. The results of the study show that the use of cooperative learning models using objects can directly improve the essay writing skills of the fifth grade students of SDIT Insan Utama Pekanbaru. The results of the students' description essay writing skills in the initial data were 56.68 which increased in UH I to 75.63 (increased by 33.43%) seen in UH II increased to 83.54 (increasing by 47.43%)